TI_GERICHTE 36.2006.180 vom 12. Oktober 2006 , Indennità giornaliera contro la perdita di guadagno. Assicurazione di danno. - TI Tribunale d'appello (2006)
Indennità giornaliera contro la perdita di guadagno. Assicurazione di danno.